2013
DOI: 10.1208/s12248-013-9458-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Device Design on the Aerosolization of a Carrier-Based Dry Powder Inhaler—a Case Study on Aerolizer® Foradile®

Abstract: Abstract. The objective of this study is to investigate the effect of device design of the Aerolizer ® on the aerosolization of a carrier-based dry powder inhaler formulation (Foradile ® ). The Aerolizer was modified by reducing the air inlet size and mouthpiece length to 1/3 of the original dimensions, or by increasing the grid voidage. Aerosolization of the powder formulation was assessed on a multi-stage liquid impinger at air flow rates of 30, 60, and 100 L/min. Coupled CFD-DEM simulations were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…Secondly, Foradil ® Aerolizer ® showed comparable FPF among the three noncoated induction ports. Zhou et al (14) reported that the detachment of drug particles from the lactose carrier surface was mainly achieved inside the inhaler prior to entering the throat. Further de-agglomeration was, therefore, not expected to take place inside the Alberta throat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, Foradil ® Aerolizer ® showed comparable FPF among the three noncoated induction ports. Zhou et al (14) reported that the detachment of drug particles from the lactose carrier surface was mainly achieved inside the inhaler prior to entering the throat. Further de-agglomeration was, therefore, not expected to take place inside the Alberta throat.…”
Section: Discussionmentioning
confidence: 99%
“…The relative contributions of the deagglomeration mechanisms for specific inhalation products are dependent upon the inhaler design and powder formulation (11)(12)(13)(14). Further de-agglomeration could, therefore, happen ex-inhaler in two ways: (i) artificial deagglomeration as particles bounce/re-entrain from the surface of an in vitro throat and (ii) de-agglomeration caused by the transient flow acceleration at the restricted region inside the Alberta throat which could occur in vivo as powder passing the mouth-throat area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes the need for the physician to know about the patient's inspiratory capacity and device performance capacity in prescribing DPI. There has been inter-and intrapatient variability in peak inhalation flow rate measurements making this selection difficult [76]. Nevertheless, the ultimate relationship between the physicochemical characteristics of the powder and the inhaler design will decide the aerosolization, de-aggregation and dispersion characteristics of the drug particles.…”
Section: Dry Powder Inhalers In Copd Lung Inflammation and Pulmonarymentioning
confidence: 99%
“…Although several in vitro apparatus such as twin-stage impinger (Haghi, Traini, & Young, 2014), multistage liquid impinger (Zhou et al, 2013) and cascade impactors (M. Chen, Romay, Li, Naqwi, & Marple, 2016) have been used to evaluate the particle deposition according to the size of particles, these methods could not totally imitate structures of upper and lower respiratory tracts. Rodent models such as rats and guinea pigs are usually employed for pulmonary dosing; however, mice are a greater technical challenge in lung dosimetry and collection of multiple blood samples due to smaller body size and limited volume of body blood.…”
Section: Animal Models For Pulmonary Dispositionmentioning
confidence: 99%